Audit of Missed Seizure Rate and Management at the Northamptonshire Healthcare (NHS) Foundation Trust ECT Clinic - Sanaa Moledina (BJPsych Open, 2025)
Aims: Missed seizures (MS) are non-therapeutic, making their frequency a key measure of an ECT clinic’s efficacy. In our initial audit at the NHFT ECT clinic (October 2021–March 2023), an MS rate of 12.6%, a restimulation rate of 67.5%, and poor adherence to the stimulus dosing protocol were identified. To address this, staff training, discussions, and dose chart displays were introduced. A follow-up audit was then conducted to assess the impact of these interventions.